1960
DOI: 10.1017/s008045680010002x
|View full text |Cite
|
Sign up to set email alerts
|

II.—On the Structure of Calymmatotheca kidstoni Calder (emended) and Genomosperma latens gen. et sp. nov. from the Calciferous Sandstone Series of Berwickshire

Abstract: SynopsisThe Lower Carboniferous fossil Calymmatotheca kidstoni Calder is shown to be a simple seed and is redescribed under the new name Genomosperma kidstoni. A second species G. latens is also described. Genomosperma gen. nov. is of interest in possessing a free nucellus with a lagenostome and short salpinx. The nucellus is surrounded by an integument of about eight lobes which are free from one another and from the nucellus from near the base of the seed. The vascular details of t h e seeds have been studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1964
1964
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 6 publications
2
53
0
Order By: Relevance
“…Early fossil seeds are usually supplied by a central terete xylem surrounded by delicate cells or cavity (decayed phloem?) [ Genomosperma kidstoni in Plate I, Figures eight (Long 41960a); Lyrasperma scotica in Plate II, Figure twenty three (Long 1960b); Dolichosperma sexangulatum in Plate IV, Figure fifty six (Long 1961); Elkinsia polymorpha in Figure fourty four (Rothwell et al 1989); Ruxtonia minuta in Plate 3, Figure 2 and Text-Figure 5f (Galtier et al 2007); Cardiocarpus samaratus in Figure twelve c (Wang et al 2003)] and they are terminal on shoots. Similar configuration has also been seen in the placental bundle in an anatomically preserved angiosperm, Beardia (Juglandaceae), from the Eocene of Canada (igures five, seven, eight of Elliott et al F2006).…”
Section: Discussionmentioning
confidence: 99%
“…Early fossil seeds are usually supplied by a central terete xylem surrounded by delicate cells or cavity (decayed phloem?) [ Genomosperma kidstoni in Plate I, Figures eight (Long 41960a); Lyrasperma scotica in Plate II, Figure twenty three (Long 1960b); Dolichosperma sexangulatum in Plate IV, Figure fifty six (Long 1961); Elkinsia polymorpha in Figure fourty four (Rothwell et al 1989); Ruxtonia minuta in Plate 3, Figure 2 and Text-Figure 5f (Galtier et al 2007); Cardiocarpus samaratus in Figure twelve c (Wang et al 2003)] and they are terminal on shoots. Similar configuration has also been seen in the placental bundle in an anatomically preserved angiosperm, Beardia (Juglandaceae), from the Eocene of Canada (igures five, seven, eight of Elliott et al F2006).…”
Section: Discussionmentioning
confidence: 99%
“…Based on what could be seen in her ground thin sections, they did not seem to differ substantially from ovules that were known from the Late Carboniferous coal-balls. It was not until Long (1959Long ( , 1960 obtained fresh examples and applied the Joy et al (1956) modification of Walton's peel technique which Calder helped pioneer, that the true significance of this material was realized. Long showed that these primitive ovules, which he renamed Genomosperma kidstonii (Calder) Long and Lyrasperma scotica (Calder) Long, were substantially different from their Late Carboniferous counterparts: they lacked a micropyle, pollen capture instead being facilitated by an apical elongation of the nucellus, known as a lagenostome or salpinx.…”
Section: Marymentioning
confidence: 99%
“…In certain Devonian and Lower Carboniferous seed ferns (e.g., Genomosperrna, Long, 1959) the integument is deeply divided into several lobes and does not circumscribe a distinct micropyle. This condition is interpreted as primitive, based on the view that the integument probably evolved by fusion of sterile "telomes" surrounding a megasporangium (Andrews, 1963).…”
Section: Micropylementioning
confidence: 99%